Walking on eggshells : what are the material risks in food retail? - Sandra Björt Kristjánsdóttir 1998-; Unnur Þórdís Kristinsdóttir 1997- (2021)
Environmental, Social, and Corporate Governance (ESG) remains a hot topic within the current business climate due to increasing transitional- and physical risks. Given the enormous scope of processes and stakeholders in the grocery retail industry, companies in the sector face a multitude of threats affecting material ESG factors. By conducting interviews with the leading supermarket chains in Iceland, this paper aims to identify the most material risks to the food retail industry, which are subsequently gathered in a materiality map. Specifically, it examines whether grocery chains prioritize specific ESG pillars rather than committing to all three. Results indicate that supply chain, data privacy, integration of ESG into financials, business ethics, sustainability disclosures, and products and services are the most likely to pose threats to grocery retailers. Additionally, it was discovered that Icelandic grocery retailers place an emphasis on the environmental pillar, while frequently overlooking the governance pillar within the ESG framework. Thus, grocery retailers are more inclined to commit to a single ESG pillar than in committing to all three.